2021
DOI: 10.1186/s12879-021-05783-8
|View full text |Cite
|
Sign up to set email alerts
|

Past eight-year malaria data in Gedeo zone, southern Ethiopia: trend, reporting-quality, spatiotemporal distribution, and association with socio-demographic and meteorological variables

Abstract: Background Informed decision making is underlined by all tiers in the health system. Poor data record system coupled with under- (over)-reporting of malaria cases affects the country’s malaria elimination activities. Thus, malaria data at health facilities and health offices are important particularly to monitor and evaluate the elimination progresses. This study was intended to assess overall reported malaria cases, reporting quality, spatiotemporal trends and factors associated in Gedeo zone,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
5
5
1
Order By: Relevance
“…This finding was consistent with findings from other investigations conducted Ethiopian. 18,19,22,26 The finding also corresponds to the monthly malaria transmission pattern reported by Ethiopia's federal ministry of health. 27 This is because high rainfall in the summer creates a perfect breeding habitat for female Anopheles mosquitos, causing malaria vector density to peak in most parts of the country from summer to autumn.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This finding was consistent with findings from other investigations conducted Ethiopian. 18,19,22,26 The finding also corresponds to the monthly malaria transmission pattern reported by Ethiopia's federal ministry of health. 27 This is because high rainfall in the summer creates a perfect breeding habitat for female Anopheles mosquitos, causing malaria vector density to peak in most parts of the country from summer to autumn.…”
Section: Discussionsupporting
confidence: 76%
“…Males were 1.69 times more likely than females to contract malaria in this retrospective analysis. Other studies done in Ethiopia 18,20,26,28 revealed greater malaria cases among males in a similar fashion. Males are more likely to contract malaria due to their involvement in outdoor activities such as agricultural and pastoral activities, as well as remaining outside during exophagic mosquito biting hours.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The results of this systematic review showed that P. falciparum and P. vivax have around 15% variation but greater variation compared to the mixed parasites. The overall estimated distribution of P. falciparum and P. vivax in the current systematic review was similar to nine of the articles included in the review [ 11 , 15 , 17 , 18 , 20 , 24 28 ] and contradict with other nine of the reviewed articles [ 8 , 10 , 12 , 16 , 19 , 21 – 23 , 27 ]. The variation in the prevalence of malaria might be related to the difference in the type of laboratory method used, methods of data collection, time of the study, and the difficulty of implementing the existing malaria prevention and control measures practice.…”
Section: Discussionsupporting
confidence: 59%
“…Conversely, our study result is higher than the findings in 11.79% in the Gedeo zone, southern Ethiopia. 33 The possible reason might be due to the differences in the study population, distribution of LLIN, and microclimatic/altitudinal differences. In addition, the relative higher malaria frequency reported might be associated with on-demand-concerted efforts toward the deployment of effective malaria prevention and control strategies in the study area.…”
Section: Discussionmentioning
confidence: 99%